A Non-structural Protein of Alfalfa Mosaic Virus in the Walls of Infected Tobacco Cells - Godefroy-Colburn, Thérèse; Gagey, Marie-Josèphe; Berna, Anne; Stussi-Garaud, Christiane (Journal of General Virology, 1986)
Summary The 32000 mol. wt. (32K) non-structural protein of alfalfa mosaic virus, P3, has previously been detected in a crude membrane fraction of infected tobacco leaves, where it accumulated transiently at the beginning of the infection period. We show here, by immunoblotting with an antiserum to a synthetic peptide corresponding to the C terminus of the protein, that the majority of P3 is in the cell wall fraction where it remains throughout infection, both at 25 °C and at 10 °C. The cell wall-associated, P3-related material is heterogeneous and contains polypeptide species of slightly lower electrophoretic mobility than the major in vitro translation product of RNA 3, which suggests that P3 may be post-translationally modified.
Keywords: cell wall